Pengungkapan Emisi Karbon dan Inovasi Hijau terhadap Nilai Perusahaan - Aning Fitriana; Destin Alfianika Maharani; Shella Rizqi Amelia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Company value is an important factor in determining the working conditions of an organization. Reflected through share prices as a form of company performance, company value is defined as a reflection of the appropriate and continuous policy setting by management so as to build market confidence in the company. The aim of the research was to understand and analyze the influence of carbon emission disclosure and green innovation on company value. The population in this research is all Sri-kehati indexed companies. Through a purposive sampling technique, the number of observations obtained in the 2020-2024 period was 84 companies. This research is included in the descriptive quantitative type category using secondary data. Annual report data is taken from www.idx.com or the company website. The technique for analyzing hypotheses applies multiple regression analysis. Research has proven that carbon emission disclosure has a positive effect on company value, and green innovation has a significant positive effect on company value. Simultaneously, disclosure of carbon emissions and green innovation influence company value..